RESEARCH ADVANCES ON FACTORS OF CORROSION AND WATER QUALITY IN DAMS: A REVIEW REPORT OF THE PROGRESS - T N, Guma; Ibrahim, Abdulkareem (Advanced Journal of Environmental Sciences (AJES), 2025)
Corrosion is a natural environmental problem that affects all our industries, products, infrastructures, equipment, systems, etc., and impacts every person, community, nation, and the entire world with shocking cost. Dams are essential for many purposes, including water supply for different uses, but they are subject to many water quality and corrosion issues. This paper reviews the corrosion factors in dams as they relate to water quality and affect the integrity status of the water distribution and infrastructural systems. The paper demonstrates from relevant research information that the quality of dam water is influenced by various chemical and physical factors that need to be monitored and controlled to achieve the required water quality and also avert corrosion of metals like steel and other material types used in dam infrastructures and water distribution systems. Corrosion linked to dam water can lead to issues like leaking in associated pipes and storage tanks as well as the leaching of toxic heavy metals into or the introduction of corrosive substances into the dam water supply, which can all reduce the water quality. The paper demonstrates further that; several factors, including temperature, pH, alkalinity, electrical conductivity, the reaction of dissolved gases (particularly oxygen and carbon dioxide) with metals, reverse osmosis-treated water, and the presence of corrosive ions like chloride, sulfate, and bicarbonate, as well as the turbulence level, flow rates, the natural composition of the water source (such as water from specific geological formations), the presence of microorganisms, changes in land use, pollution in the catchment area, etc., influence both corrosion and water quality in dams. The review information is pertinent for researchers, students, stakeholders, corrosion and quality control strategists, etc., in their varied endeavors to achieve the quality standards of dam waters and preserve the integrity of all system components that must be in service contact with dam waters.